Shared Decision-Making in Patients with an Abdominal Aortic Aneurysm or Peripheral Artery Disease: A Scoping Review - Kooijman, Maria-Annette; van Leeuwen, Goudje L.; Schuurmann, Richte C.L.; van Leeuwen, Barbara L.; van Munster, Barbara C.; van der Wal-Huisman, Hanneke; de Vries, Jean-Paul P.M. (Annals of vascular surgery, 2025)
This review provides an overview of the literature on shared decision-making (SDM) in patients with abdominal aortic aneurysm (AAA) or peripheral artery disease (PAD) and identifies barriers and facilitators. A systematic scoping review was conducted, in which 4 databases were systematically searched for the period January 2007 to November 2024. All articles were reviewed by 2 independent authors and asses for quality using the mixed-methods appraisal tool (MMAT). The literature search yielded 15,738 articles, of which 50 met the inclusion criteria. Quality assessment via MMAT showed good quality in 70% of the studies. Various influencing factors were revealed on SDM in patients, physicians, consult content, and the system or organization of care. Despite increased attention, implementing SDM in AAA and PAD patients remains challenging due to healthcare professionals' limited understanding of SDM. Patients seek active involvement but often feel inadequately engaged. There is a notable lack of research focusing on health care professionals and systemic influences on SDM. •Patients express a desire for active involvement in decision-making; yet, many feel inadequately engaged during consultations.•Factors, such as age, comorbidities, and health literacy, play significant roles in shaping patients' engagement levels.•Healthcare professionals have limited understanding of what shared decision-making (SDM) entails.•There is a notable lack of research focusing on health care professionals and systemic influences on SDM.•There is a need for improved communication, education, and training on SDM in these fields of vascular surgery.